ปัจจัยที่มีผลต่อระบบขยายพันธุ์สตรอเบอรีพันธุ์พระราชทาน 80 และพันธุ์ 329 ในสภาพปลอดเชื้อ - โทปุญญานนท์, นพมณี; อุตตมะ, น้ำฝน; แก้วดำ, ธนาภรณ์ (Thai Journal of Science and Technology, 2019)
Abstract Micropropagation of strawberry is now widely accepted as it is able to produce disease-free, healthy, good quality plants, and a number of plants increases at a faster rate. As such, this study was focused on various factors that may affect the micropropagation of two cultivars of strawberry (cv. Praratchatan 80 and cv. 329). In initiation stage, factors influencing initiation were investigated including strawberry cultivars, disinfestation chemicals and 3 developmental stages of runner. The results showed that 0.1 % HgCl2 is the most effective disinfectant for strawberry cv. Praratchatan 80 at leaf-closed runner stage with 100 % survival rate, and for strawberry cv. 329 with 90-100 % survival at every developmental stages. During multiplication stage, suitable types and concentrations of cytokinins were studied. Results showed that 0.5 mg/L TDZ was the best for increasing the number of shoots per cluster on strawberry cv. Praratchatan 80 (38.75 plants) and cv. 329 cultivars (24.2 plants). Meanwhile, during the rooting stage, types and concentrations of auxin were observed. Results showed that 0.3 mg/L IBA is the best on inducing rooting, but roots are short. Although NAA could induce roots but callus occurred at the base, which appeared disconnection between shoot and roots. Keywords: micropropagation system; strawberry; plant quality